거골 골연골 병변에 대한 미세 골절술 실패 후 2차 치료로서 자가연골 세포 이식술 - 김진수; Kim, Jin Su (대한족부족관절학회지, 2015)
Microfracture as a reparative strategy is the treatment of choice for an osteochondral lesion of talus. Although the results of microfracture are generally excellent, at least 30% of patients who received microfracture have acute or chronic ankle pain with several or unknown causes. The most important factor for unsatisfactory outcome after microfracture is the size of the lesion. For failed osteochondral lesion of talus, the second options are autologous osteochondral graft, autologous chondrocyte implantation, or re-microfracture. In this article, we present the autologous chondrocyte implantation as a second procedure for failed microfracture and compare its clinical outcome with other methods based on a literature review.